Settler Colonialism and Indigenous Diplomatic Resistance in Palestine (1882 to 1914) - Shamikh Badra (State Crime)
This article contributes to the study of settler colonialism and Indigenous resistance by introducing a novel framework: “Indigenous Diplomatic Resistance” (IDR). Michel Foucault’s theories are useful for highlighting how Indigenous groups use diplomatic channels to resist settler-colonial domination. By applying settler colonialism theory to the Palestinian case, this article offers new insights into Palestinian resistance against colonial Zionism, especially in the time of Jewish immigration between 1882 to 1914. Foucault’s notion of discursive power underscores how colonial powers impose knowledge systems that justify control, whilst Indigenous peoples push back through alternate forms of knowledge, including diplomatic strategies ( Foucault 2003 : 23–24). This article challenges narratives that focus on military or grassroots resistance, suggesting that Palestinian diplomatic resistance was central to their resistance strategy. This approach provides a new lens through which to understand the nature of Palestinian resistance, emphasizing the epistemic struggle inherent in their fight against settler colonialism.